WHEN ENGAGING LEARNING IS NOT ENOUGH: EXPLORING THE ROLE OF RULE AND COMPLIANCE BASED CLASSROOM MANAGEMENT IN DISRUPTIVE CLASSROOMS - Christabell Hasibuan; Ni Luh Sekar Astuti (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2026)
This study examines the limitations of engaging, experience-based learning in managing disruptive classrooms and explores how teachers respond through rule- and compliance-based classroom management. Using a qualitative literature review, the study synthesizes conceptual and empirical sources on disruptive behavior, meaningful learning, emotional safety, and structured classroom management. John Dewey’s experiential learning theory serves as the primary theoretical lens, particularly his emphasis on meaningful experience, continuity, and responsibility. The findings indicate that engaging learning can reduce disruption when activities are meaningful, well designed, and supported by a psychologically safe environment. However, engagement alone often fails when students lack self-discipline, learning awareness, and emotional regulation. In such contexts, clear rules, routines, supervision, and consistent consequences provide the stability necessary for responsible participation. The study refines Dewey’s framework through the concept of internal student capital and argues that effective classrooms require meaningful learning, emotional safety, and clear structure operating together.